2006
DOI: 10.1159/000089883
|View full text |Cite
|
Sign up to set email alerts
|

Extensive gross genomic rearrangements between chicken and Old World vultures (Falconiformes: Accipitridae)

Abstract: The karyotypes of most birds consist of a small number of macrochromosomes and numerous microchromosomes. Intriguingly, most accipitrids which include hawks, eagles, kites, and Old World vultures (Falconiformes) show a sharp contrast to this basic avian karyotype. They exhibit strikingly few microchromosomes and appear to have been drastically restructured during evolution. Chromosome paints specific to the chicken (GGA) macrochromosomes 1–10 were hybridized to metaphase spreads of three species of Old World v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 58 publications
4
54
0
Order By: Relevance
“…Comparative chromosome painting in the whitethroated sparrow: Studies focused on the evolution of avian karyotypes have been advanced by the development and utility of chicken (Gallus gallus) chromosome paints for comparative mapping (ZOO-FISH) in a diverse sampling of birds (Shetty et al 1999;Guttenbach et al 2003;Itoh and Arnold 2005;Nanda et al 2006;Nishida-Umehara et al 2007). Those efforts and other gene-based comparative mapping studies (Backstrom et al 2006;Itoh et al 2006) have demonstrated that conserved synteny among birds is quite extensive with many chicken chromosomes displaying a one-to-one orthologous relationship to chromosomes from other species, including passerines (Guttenbach et al 2003;Derjusheva et al 2004;Itoh and Arnold 2005), which diverged from the chicken lineage $100 million years ago (MYA) (van Tuinen and Hedges 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Comparative chromosome painting in the whitethroated sparrow: Studies focused on the evolution of avian karyotypes have been advanced by the development and utility of chicken (Gallus gallus) chromosome paints for comparative mapping (ZOO-FISH) in a diverse sampling of birds (Shetty et al 1999;Guttenbach et al 2003;Itoh and Arnold 2005;Nanda et al 2006;Nishida-Umehara et al 2007). Those efforts and other gene-based comparative mapping studies (Backstrom et al 2006;Itoh et al 2006) have demonstrated that conserved synteny among birds is quite extensive with many chicken chromosomes displaying a one-to-one orthologous relationship to chromosomes from other species, including passerines (Guttenbach et al 2003;Derjusheva et al 2004;Itoh and Arnold 2005), which diverged from the chicken lineage $100 million years ago (MYA) (van Tuinen and Hedges 2001).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the slow rate of chromosome rearrangements in most of bird species (Burt et al 1999), chromosomes have been drastically reconstructed in Accipitridae of the Falconiformes. Chromosome painting with chicken probes for four Accipitridae species, the Harpy eagle (Harpia harpia) (de Oliveria et al 2005) and three Old World vultures (Gyps ruppelli, Gyps fulvus and Gypaetus barbatus) (Nanda et al 2006), confirmed the dramatic reduction of microchromosomes by fusions and translocations of microchromosomes and the increase of bi-armed medium-and small-sized macrochromosomes by repeated fission and fusion events and many other types of rearrangements in macrochromosomes.…”
Section: Introductionmentioning
confidence: 93%
“…Lately, chromosome-specific DNA painting probes for chromosomes 1-9 and Z and fractions of microchromosomes have been developed in chicken (Gallus gallus domesticus) , Habermann et al 2001, Masabanda et al 2004. To date, comparative chromosome painting with the chicken probes has been performed for a total of 40 species from 10 orders (Shetty et al 1999, Schmid et al 2000, Raudsepp et al 2002, Guttenbach et al 2003, Kasai et al 2003, Derjusheva et al 2004, Shibusawa et al 2004a, b, de Oliveria et al 2005, Itoh & Arnold 2005, Nanda et al 2006, Nishida-Umehara et al 2007). These results revealed that the avian karyotypes are highly conserved at the molecular level, and that the typical avian karyotype with a small number of macrochromosomes and a large number of microchromosomes is mostly conserved and hence representative of the ancestral state.…”
Section: Introductionmentioning
confidence: 99%
“…The karyotypes of Anseriformes are characterized by high diploid chromosome numbers (2n=78-84), consisting of a small number of macrochromosomes and numerous indistinguishable microchromosomes (Christidis, 1990). This typical avian karyotype is widely conserved in all palaeognathous and most neognathous bird species (Takagi and Sasaki, 1974;Belterman and de Boer, 1984;Nishida-Umehara et al, 2007); in contrast, the atypical karyotype, characterized by a lower diploid chromosome number, no large macrochromosomes, many medium-sized and small chromosomes, and only a few pairs of microchromosomes, are commonly found in accipitrid species (Amaral and Jorge, 2003;de Oliveira et al, 2005de Oliveira et al, , 2010Nanda et al, 2006;Nishida et al, 2008Nishida et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%